Effect of the organoclay preparation on the extent of intercalation/exfoliation and barrier properties of polyethylene/PA6/montmorillonite nanocomposites - Erdmann, Eleonora (2010)
Nanocomposites of HDPE matrix and 3 wt % organoclay/PA6 discontinuous phase were prepared in a mixer chamber. These nanocomposites of organoclay, PA6, and HDPE were characterized by X-ray diffraction, scanning electron and transmission electron microscopy (SEM and TEM). Barrier properties were determined by cyclohexane pervaporation and solubility. The results show that the degree of exfoliation and/or intercalation and the barrier properties depend on a combination of the proper chemical treatment and optimized processing in these polyethylene-organoclays nanocomposites.